Love-Based Curriculum: Fostering Islamic Eco-theology Education in Madrasah: Fostering Islamic Eco-theology Education in Madrasah - Rifqi, Muhammad Ichsan; Saputra, Aria (LPPM Universitas Ibn Khaldun, Bogor, 2025)
Madrasahs have the potential to produce a generation of Muslims who care about nature conservation through a love-based curriculum that is integrated with Islamic ecotheology. This research aims to analyze the integration of ecotheological principles into the love-based curriculum in madrasah, as well as how strategies in implementing Islamic-based environmentally friendly education in learning in madrasah. This research uses a qualitative method with a literature study design. Based on the analysis of the love-based curriculum and Islamic ecotheology, there is a harmony of principles between the two, namely the principles of tauhid, khalîfah, amanah, mîzan, and rahmatan lil âlamîn. As for the implementation strategy of Islam-based environmentally friendly education through a love-based curriculum, educators can pay attention to several aspects such as teaching modules, participatory learning approaches and models, and learning evaluation. Environmentally friendly practices can take the form of intracurricular or extracurricular activities. This research proves that through the integration of Islamic ecotheology in a love-based curriculum, madrasas have the potential to produce a generation of Muslims who are aware of the importance of environmental conservation